Reflex Sympathetic Dystrophy Syndrome of the Ankle in Pregnancy - Mehmet Karakoç,; Özlem Altındağ,; Neslihan Soran, (Archives of Rheumatology, 2007)
Reflex sympathetic dystrophy (RSDS) is a type of arthropathy combining a painful syndrome with regional trophic disturbances. The condition primarily affects women during pregnancy, but it also affects middle-aged men. Although hip involvement is the most common form of the disease in pregnancy, other joints such as knee and ankle may be involved. Diagnosis is based on typical clinical and radiological observations. Pain may persist for six months or longer. Fracture is the major risk for the disease. Treatment consists of analgesics, protection against stress fractures, and the prevention of contractures. Reflex sympathetic dystrophy does not appear to affect the course of pregnancy but conclusion of the pregnancy is necessary for cure. We described a patient with pain and local osteopenia of the ankle occurring in the third trimester of pregnancy. We prefer the name reflex sympathetic dystrophy for this condition and we discussed the different terms which determine the same condition. (Rheumatism 2007; 22: 76-9)